Cell-specific epigenome-wide DNA methylation profile in long-term cultured minor salivary gland epithelial cells from patients with Sjögren's syndrome. Issue 3 (16th January 2017) - Charras, Amandine; Konsta, Orsia D; Le Dantec, Christelle; Bagacean, Cristina; Kapsogeorgou, Efstathia K; Tzioufas, Athanasios G; Pers, Jacques-Olivier; Bordron, Anne; Renaudineau, Yves
Abstract : Objectives: The aetiology of primary Sjögren's syndrome (pSS), also referred to as autoimmune epithelitis, is incompletely understood but includes an epigenetic contribution. Accordingly, the aim of this study was to investigate DNA methylation in salivary gland epithelial cells (SGEC), and to compare results with those publicly available from pSS B and T cells. Methods: Long-term cultured SGEC were selected to conduct an epigenome-wide association study (EWAS) in patients with pSS with comparison to controls using the HumanMethylation 450 K array from Illumina. Results: The analysis of differentially methylated CpG (DMC) uncovered 4662 positions corresponding to 2560 genes, and 575 genes with two or more DMC sites (DMCs), in SGEC as compared with controls. Further analysis highlighted an important proportion of interferon-regulated genes (61%), the calcium pathway (hypomethylated) and the Wnt pathway (hypermethylated). When comparing SGEC with pSS T and/or B cell results, an important overlap was observed with respect to differentially methylated genes (38.8%) and pSS risk factors (71.4%), although such assertion was not true when comparing DMCs. Conclusions: This study conducted in SGEC emphasises the role of DNA methylation in pSS pathogenesis and supports the necessity to conduct pure cell analysis for future EWAS studies when analysing salivary glands from patients with pSS.